Tunnel method in laparoscopic single-position nephroureterectomy for women: preserving the uterine round ligament during distal ureter management and bladder cuff excision - Wang, Fangming; Yang, Feiya; Guo, Yansong; Xing, Nianzeng; Li, Jianxing (Frontiers in Surgery, 2026)
This study introduces a novel “tunnel method” for single-position laparoscopic nephroureterectomy in women with upper urinary tract urothelial carcinoma (UTUC), enabling complete resection of the kidney and entire ureter while preserving the uterine round ligament during dissection of the intramural ureter and bladder cuff excision. By creating a tunnel-like space beneath the round ligament via precise dissection of the uterine broad ligament, this technique avoids round ligament transection, thereby maintaining pelvic anatomical integrity, reducing risks of pelvic organ prolapse, minimizing postoperative adhesions, and preserving reproductive and pelvic function-particularly critical for women of childbearing age or those at risk of prolapse. This innovative approach ensures effective oncological resection while prioritizing female-specific anatomical and functional considerations, providing a more comprehensive and patient-centered treatment option for UTUC.